The: Impact of the Digital Revolution on Fashion Marketing and Communication Strategies - Laiba Arshad,; Shaikh Shahrya,; Nabeel Tahi, (Journal of Peace, Development and Communication, 2024)
The major shift of media and digital platforms has changed the meaning of fashion causing a drastic change in fashion businesses. This study examines on how digital technology has impacted fashion marketing and its communication strategies. Media evolution which is a major reason of fashion business shift from traditional to digital platforms and has changed the medium of communication to connect with the customers, promotion of their products and brand identity, all the meanings have been changed. This shift created a chaos among the emerging or small designer who don’t have access to excessive knowledge and technological advancement. This article will analyse all the key aspects of the digital trends and virtual experiences of the renowned and emerging brands and customers. Highlighting which elements have become important for digital fashion, how and what to adopt for the latest fashion marketing and communication strategies.